RESPON TANAMAN JAGUNG YANG DIPUPUK BIO-FOSFAT DI ANDISOLS - Yudi Sastro -; Irfan D. Prijambada -; Dja’far shiddieq - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2007)
This experiment was aimed to find out the effect of the pellet fertilizer combining of rock phosphate, organic material, and Aspergillus niger inoculums (bio-phosphate fertilizer) on maize growth and its phosphorus uptake in Andisols. The study was conducted in green house of Faculty of Agriculture of Gadjah Mada University using plastic pots containing 5 kg of Andisols from Salatiga, Central Java. The treatments were bio-phosphate, the pellet of rock phosphate and A. niger, the pellet of rock phosphate and organic material, the pellet of rock phosphate, super phosphate, and without phosphorus fertilizer arranged using Completely Randomized Design with five replications. Arjuna maize was plant indicator. The results indicated that the bio-phosphate fertilizer increased the maize growth and its phosphorus uptake in Andisols up to 32.0% and 65.1% compared without phosphate fertilizer, respectively. Keywords: phosphorus, bio-phosphate, Andisols, maize